Analysis Of Communications And Incentives On Nurse Performance In Inpatient Rooms In Royal Prima Marelan General Hospital - Imelda Sembiring; Muhammad Faridz Syahrian; Sri Lestari (International Journal of Health and Pharmaceutical (IJHP), 2024)
One of the factors that influence the success rate of a hospital is the performance of nurses. Efforts to improve nurse performance include paying attention to nurse work stress. This study aimed to determine the effect of communication and incentives on nurse performance in the inpatient room of the Royal Prima Maryland General Hospital. The type of research used is cross-sectional survey research with an explanatory research method approach. The total population is 41 nurses; all nurses are used as respondents (complete sampling). Data were analyzed using the Chi-square test, and logistic regression was used to obtain the OR (Odds Ratio) value. The results showed a statistical relationship between communication and performance (p = 0.012), and the OR value was 6.708, meaning that nurses with good communication would increase their performance by 6.7 times. Providing incentives on performance (p = 0.006) and the OR value is 6.667, meaning nurses with incentives will improve performance by 6.6 times. Income on performance (p = 0.004) and the OR value is 8.762, meaning nurses with incentives will increase performance by 8.7 times. The hospital should conduct periodic counseling and distribute questionnaires as evaluation material and material for stress management for nurses every three months.